2022
DOI: 10.1039/d1nr06456h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced degradation in AgBiS2 nanocrystal solar cells

Abstract: AgBiS2 nanocrystal solar cells are among the most sustainable emerging photovoltaic technologies. Their environmentally-friendly composition and low energy consumption during fabrication make them particularly attractive for future applications. However, much...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…[25] However, our previous studies examining the degradation behavior of AgBiS 2 showed that the high binding energy peak is associated with Bi 2 O 3 since upon exposure to the oxygen of the QD films, its relative contribution to the Bi spectrum grew substantially. [58] This assignment to Bi 2 O 3 is further corroborated by the presence of a strong peak at 529.6 eV in the O 1s spectra measured on the (TMS) 2 S samples, which is consistent with a metal oxide (Figure 5c). On the other hand, the synthesis with St 2 S results in a single Bi species at 158.1 eV, indicating that no Bi 2 O 3 is formed.…”
Section: Morphological and Compositional Analysissupporting
confidence: 58%
“…[25] However, our previous studies examining the degradation behavior of AgBiS 2 showed that the high binding energy peak is associated with Bi 2 O 3 since upon exposure to the oxygen of the QD films, its relative contribution to the Bi spectrum grew substantially. [58] This assignment to Bi 2 O 3 is further corroborated by the presence of a strong peak at 529.6 eV in the O 1s spectra measured on the (TMS) 2 S samples, which is consistent with a metal oxide (Figure 5c). On the other hand, the synthesis with St 2 S results in a single Bi species at 158.1 eV, indicating that no Bi 2 O 3 is formed.…”
Section: Morphological and Compositional Analysissupporting
confidence: 58%
“…In summary, a directional amplification of the photoluminescence from perovskite-based metasurfaces was demonstrated, providing the important prerequisites for a spatially selective outcoupling of emission for light-emitting diodes, backlight displays, and nanometer-sized distributed feedback lasers. The proposed optimization of the confinement self-assembly technique suggests a cost-efficient approach for manufacturing metasurfaces over large areas under ambient conditions, featuring periodicities from hundreds of nanometers up to micrometers, and making it applicable for materials, emitting light in a wide spectral range from blue to the near-infrared regions, , or utilizing environmentally friendly quantum dots . Moreover, we implemented a profound polarization- and angle-resolved spectroscopic examination, supported by the numerical simulations, explaining the origins of the observed optical effects and suggested a strategy for the rational design of the metasurfaces by maximizing the spectral overlap of the emission of perovskite nanocrystals with the diffracted and guided modes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen and light can further accelerate the degradation rate. [66][67][68][69] HTLs should have good hole mobility, compatible energy levels (valence band maximum), thermal/photochemical stability and low cost. These components continuously regenerate charge carriers and inuence the inner charge transfer between the cathode and anode.…”
Section: Influence Of Adjacent Charge Transport Layersmentioning
confidence: 99%
“…Organic HTLs like PTB7 have a major impact on the instability of AgBiS 2 NC devices due to the breakdown of the organic extraction layers. 71 These organic HTLs tend to degrade quickly, with a direct impact on the device stability and photodynamics. Our analysis on all devices with organic HTLs indicates that they tend to stimulate the degradation and relatively quicken the degradation time in these devices, containing organic HTLs.…”
Section: Influence Of Adjacent Charge Transport Layersmentioning
confidence: 99%